Exome sequencing improves genetic diagnosis of congenital orofacial clefts - Yan, Shujuan; Fu, Fang; Li, Ru; Yu, Qiuxia; Li, Fucheng; Zhou, Hang; Wang, You; Huang, Ruibin; Ma, Chunling; Guo, Fei; Wang, Dan; Yang, Xin; et al. (Frontiers in Genetics, 2023)
Objective: This retrospective study aims to evaluate the utility of exome sequencing (ES) in identifying genetic causes of congenital orofacial clefts (OFCs) in fetuses with or without other structural abnormalities, and to further explore congenital OFCs genetic causes. Methods: The study enrolled 107 singleton pregnancies diagnosed with fetal OFCs between January 2016 and May 2022, and categorized them into two groups: isolated cleft lip and/or palate (CL/CP) and syndromic CL/CP. Cases with positive karyotyping and chromosomal microarray analysis results were excluded. Whole-exome sequencing was performed on eligible fetuses and their parents. Monogenic variants identified by ES and perinatal outcomes were recorded and evaluated during postnatal follow-up. Results: Clinically significant variants were identified in 11.2% (12/107) of fetuses, with no significant difference in detection rate between the isolated CL/CP group and the syndromic CL/CP group (8/83, 9.6% vs. 4/24, 16.7%, p = 0.553). Additionally, sixteen (16/107, 15.0%) fetuses had variants of uncertain significance. We identified 12 clinically significant variations that correlated with clinical phenotypes in 11 genes from 12 fetuses, with CHD7 being the most frequently implicated gene (n = 2). Furthermore, we observed a significant difference in termination rates and survival rates between the isolated CL/CP and syndromic CL/CP groups (41.0% vs. 70.8% and 56.6% vs. 20.8%, p＜0.05 for both). Conclusion: Based on our findings, it is clear that ES provides a significant increase in diagnostic yield for the molecular diagnosis of congenital OFCs, thereby substantially improving the existing prenatal diagnostic capabilities. This study also sheds light on seven novel pathogenic variants, broadening our understanding of the genetic underpinnings of OFCs and expanding the disease spectrums of relevant genes.